Practice education and the pandemic: Possibilities and challenges in the adoption of a virtual pedagogy - Short, Christopher (The Journal of Practice Teaching and Learning, 2023)
The corona virus pandemic presented a significant disruption to social work education (Wolf et al, 2020; McLaughlin et al, 2020). Research that emerged from the pandemic offers valuable insight into the possibilities for students and the efficacy of new virtual teaching methods. Yet our current understanding lacks the perspective of the practice educator, tasked with navigating students through placement. This article outlines the findings of a practitioner research project that sought to understand the experiences of practice educators within one Teaching Partnerships of the south eastern region of England during the pandemic, and the role technology played in delivering social work education virtually. Within this qualitative study data was gathered through semi-structured interviews with four independent practice educators. Interviews were transcribed and analysed using thematic analysis. Practice educators encountered phenomena on placement that generated considerable uncertainty and disruption. Educators then sought to ‘make sense’ of the interaction between these phenomena and the emotional experiences they evoked. As physical access to the practice learning context was prohibited, practice educators also found themselves engaged in finding creative means to becoming digitally present.